2014
DOI: 10.1007/s11130-014-0406-0
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins, Phenolic Acids and Antioxidant Properties of Juçara Fruits (Euterpe edulis M.) Along the On-tree Ripening Process

Abstract: Juçara (Euterpe edulis M.) fruits are an interesting source of phenolic compounds, mainly anthocyanins, making them valuable to the food and pharmaceutical industries. Juçara fruits were harvested along the on-tree ripening process between March and June as practiced in Paraná state, Brazil and examined for their total anthocyanin content (TAC), total phenolic content (TPC), total phenolic acid (TPA) and total antioxidant capacity (TAA). Overall, TAC increased (91.52-236.19 mg cyanidin-3-glucoside equivalent/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 21 publications
9
66
6
Order By: Relevance
“…Physicochemical characteristics, bioactive compounds and antioxidant capacity of banana, strawberry and juçara pulps. anthocyanins content represented, in majority, by cyanidin-3-rutinoside (Bicudo et al, 2014).…”
Section: Pulps Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicochemical characteristics, bioactive compounds and antioxidant capacity of banana, strawberry and juçara pulps. anthocyanins content represented, in majority, by cyanidin-3-rutinoside (Bicudo et al, 2014).…”
Section: Pulps Characterizationmentioning
confidence: 99%
“…Juçara (Euterpe edulis Martius), a typical palm from Brazilian Atlantic Forest, produces fruits rich in compounds potentially antioxidants such as the anthocyanins (Bicudo et al, 2014;Schulz et al, 2015). On Brazilian market products containing high amounts of juçara or açaí pulp are very well accepted, which is not observed in the foreign market.…”
Section: Introductionmentioning
confidence: 99%
“…However, interest in these berries has arisen particularly due to their high in vitro antioxidant properties, attributed to their high content of phenolic compounds, such phenolic acids, anthocyanins and other flavonoids (Bicudo, Ribani, & Beta, 2014;Borges et al, 2013;Cardoso et al, 2015;De Brito et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, phenolics are generally associated with health-promoting properties and the prevention of several degenerative diseases (Oroian & Escriche, 2015). The results of several studies have indicated that juçara fruit may exert antioxidant effects in vitro (Bicudo et al, 2014;Borges et al, 2011;Vieira, Cavalcanti, Meireles, & Hubinger, 2013) and in an animal model (De Castro et al, 2014). The extract from juçara berries also exhibits strong antioxidant activity and antiproliferative activity against Vero cells (Borges et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These data show that the extract in ethanol has antioxidant ability expressively higher than that of the extract in hexane. This is possibly related to the fact that phenols compounds known for their good antioxidant ability (Boulekbache-Makhlouf et al, 2013;Bicudo et al, 2014), are present in a higher proportion in the ethanol extract, justifying the result. The antioxidant capacity of various tropical fruits was studied by Rufino et al (2010), who reported the pulp of the fruit of carnauba presented a high antioxidant activity of 3549±184 g/g DPPH, for the fresh matter and 4877±24.30 g/g DPPH, based on DM.…”
Section: Resultsmentioning
confidence: 87%